Tropical development : 1880-1913 - Lewis, W. Arthur (London : George Allen & Unwin, 1970)
This comprise of essays prepared during the year 1967-8 by members of Woodrow Wilson School that examine various theories of development and analysing the progress of less developed countries during the 1950s and 1960s. Topics and issues covered include: export stimulus; tropical exports; Colombia; Brazil; Venezuela; Gold Coast (now Ghana) and Nigeria; Kenya and Uganda; Egypt; Ceylon (now Sri Lanka); Indonesia; the Philippines and India.
Essays prepared during the year 1967-8 by members of a graduate seminar in the Woodrow Wilson School, Princeton University.
Includes bibliographical references and index.
lje 10/05/2018
Loans
Keywords: Economic development; Tropics; Developing countries